Internal conflicts : a four state analysis (India, Nepal, Sri Lanka, and Myanmar) - Raghavan, V.R.; Raghavan, V. R.; Centre for Security Analysis (Chennai, India); Internal Conflicts and Transnational Consequences (Project) (2013)
Contributed articles.
Copyright: Centre for Security Analysis, Chennai, India.
"The Centre for Security Analysis (CSA) has undertaken a three year research project Internal Conflicts and Transnational Consequences supported by the John D. and Catherine T. MacArthur Foundation. This volume is part of the ongoing project and its publication has been possible by the project grant"--Acknowledgement.
Keywords: Social conflict -- India; Social conflict -- Nepal; Social conflict -- Sri Lanka; Social conflict -- Burma; Internal security; Ethnic conflict; Counterinsurgency